Implementation of Creative Character of Students Through Double Track Program at SMA Negeri 1 Dawarblandong Mojokerto - Ayulusiana, Winda Eka; Srinarwati, Dwi Retnani (Universitas Tanjungpura, 2025)
Double Track is the implementation of teaching and learning activities in its implementation referring to providing skills for high school students who do not continue to college.This research aims to describe the implementation of character education at SMA Negeri 1 Dawarblandong, describe the implementation of the Double Track Program at SMA Negeri 1 Dawarblandong, and analyze the implementation of students' creative character through the Double Track Program at SMA Negeri 1 Dawarblandong. This research uses a qualitative descriptive research approach. Data collection techniques use observation, interviews, documentation and questionnaires. The research subjects were Deputy Head of Curriculum, Deputy Head of Public Relations, religion teachers, PPKn teachers, Double Track Program administrators/facilitators, Double Track trainers, and students taking part in the Double Track Program. Validity of data using triangulation of sources and techniques. Data analysis uses qualitative analysis with mechanisms for data collection, data reduction, data presentation, and drawing conclusions. The results of the research reveal that the implementation of character education at SMA Negeri 1 Dawarblandong has been implemented well, namely through teaching and learning activities in each subject. Apart from being taught character education, students are also provided with skills, namely through the Double Track Program. The implementation of the Double Track Program at SMA Negeri 1 Dawarblandong Mojokerto has gone according to plan. Implementation is carried out according to a pre-arranged schedule. This form of implementing students' creative character through the Double Track Program is carried out when the Double Track Program training is in progress.